Evaluation Of Coverage and Compliance of Mass Drug Administration Programme 2011 For Elimination of Lymphatic Filariasis in Nalgonda District Of Andhra Pradesh, India - Nirgude , Abhay S; Naik , Poonam R; Kondagunta , Nagaraj; Reshmi , Sidramappa S; Takalkar , Anant A; Prasad , VG (National Journal of Community Medicine, 2012)
Background and Objectives: Lymphatic Filariasis has been a major public health problem in India next only to malaria. Government of India during 2004 initiated Mass DrugAdministration (MDA) with annual single dose of DEC tablets to all the population living atthe risk of Filariasis. Mass Drug Administration of Diethyl Carbamazine (DEC) &Albendazole (ALB) was undertaken in 16 districts of Andhra Pradesh on 9th, 10th and 11th December 2011. Present study aimed to evaluate coverage and compliance rate of Mass Drug Administration for lymphatic Filariasisin Nalgonda district of Andhra Pradesh. Methods: Community Based cross-section study was undertaken among four selected clusters of Nalgonda district as per National Vector Borne Disease Control Programme (NVBDCP) guidelines. Information pertaining to coverage and compliance of MDA was gathered from 120 families from 4 clusters by interview technique using structured questionnaire. Results: The average family size was 4.21 and majority of the respondents were males and of more than 15 years of age. The eligibility, coverage and compliance rates were 96.2%, 79.7% and 43.04% respectively. On the spot consumption of tablets was reported by only 22.9% respondents. Most common cause for non-compliance was fear of side effects (47.5%).I E C activity was reported to be seen by only 21.7% respondents. Conclusion: Improving the community compliance in DEC consumption is the major challenge. There is an urgent need for effective MDA strategy with emphasis on Advocacy, social mobilization and monitoring.